RESPON PERTUMBUHAN VEGETATIF DAN GENERATIF WORTEL TERHADAP PEMBERIAN DOSIS DARI BERBAGAI JENIS PUPUK KANDANG - Rina C. Hutabarat; Susilawati Barus (JURNAL AGROTEKNOSAINS, 2018)
Carrots are horticultural plants that have high economic value opportunities because every year the demand for carrots both domestically and abroad needs to increase continuously, but not maximum productivity due to the provision of organic fertilizers that are not balanced with chemical fertilizers in the soil. The research objective was to obtain animal manure fertilizer with the best dosage of fertilizer for growth and yield of carrots as an alternative to mixing chicken manure. The study was carried out in the berastagi experimental garden in February to May 2018. The experiment was arranged based on a 2-factor complete randomized trial design namely: the first factor is the type of organic animal waste pesticides consisting of H0 = Control / without treatment, H1 = chicken manure, H2 = cow / cow dung, H3 = horse manure and H4 = goat manure. The second factor is the level / dose used, namely K0 = control, K1 = 500 g / 2 m2, K2 = 1000/2 m2 repeated 3 times. Carrot samples per plot of 200 tubers. The observed variables:) Percentage of living plants (60 days), 2) Number of Compound Leaves, 3) Plant Height, 4) Wet yield weight per plot (kg) and 5) Root tuber length (cm). The results showed that the administration of organic fertilizer from cow manure had a significant effect on all parameters, namely growth percentage, plant height, yield weight and root tuber length. The dose of animal manure organic fertilizer is ideal for growth and production of carrots, which is 500 gr / 2 m2.